2006
DOI: 10.1111/j.1745-6916.2006.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mathematically Precocious Youth After 35 Years: Uncovering Antecedents for the Development of Math-Science Expertise

Abstract: This review provides an account of the Study of Mathematically Precocious Youth (SMPY) after 35 years of longitudinal research. Findings from recent 20-year follow-ups from three cohorts, plus 5- or 10-year findings from all five SMPY cohorts (totaling more than 5,000 participants), are presented. SMPY has devoted particular attention to uncovering personal antecedents necessary for the development of exceptional math-science careers and to developing educational interventions to facilitate learning among inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
446
2
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(479 citation statements)
references
References 107 publications
(245 reference statements)
19
446
2
12
Order By: Relevance
“…The most obvious answer is that the choice of achievement domain is determined by a great many more variables than just those relevant to hierarchical placement and creative performance. Examples include special ability patterns and vocational interests (see, e.g., Achter, Lubinski, Benbow, & Eftekhari-Sanjani, 1999;Lubinski & Benbow, 2006;Park, Lubinski, & Benbow, 2007). Because these additional factors are differentially dependent on diverse genetic and environmental influences, they may operate in a manner largely orthogonal to the dispositional and developmental variables emphasized in the hierarchical model.…”
Section: Resultsmentioning
confidence: 99%
“…The most obvious answer is that the choice of achievement domain is determined by a great many more variables than just those relevant to hierarchical placement and creative performance. Examples include special ability patterns and vocational interests (see, e.g., Achter, Lubinski, Benbow, & Eftekhari-Sanjani, 1999;Lubinski & Benbow, 2006;Park, Lubinski, & Benbow, 2007). Because these additional factors are differentially dependent on diverse genetic and environmental influences, they may operate in a manner largely orthogonal to the dispositional and developmental variables emphasized in the hierarchical model.…”
Section: Resultsmentioning
confidence: 99%
“…Inevitably, ICM has been applied in a variety of educational settings and among gifted populationwhereby the application of acceleration and mentoring as curriculum strategies-with huge success. To illustrate, a number of studies found positive effects of acceleration on gifted students in terms of academic performance, opportunity for early college admission, and socio-emotional development (Rinn, 2007;Lubinski & Benbow, 2006;Stanley, 2000;Cornell et al, 1991;Brulles et al, 2010). On a similar note, studies by Noriah (2012), Irving et al (2003) and Chan (2000) revealed that mentoring can become an effective gifted programming strategy-to facilitate the students' academic achievement, career determination, and psychosocio-emotional growth-provided that critical factors mentioned below were taken into consideration: 1) Objectives of the mentoring program are clarified to both mentor and protégé/mentee.…”
Section: Resultsmentioning
confidence: 99%
“…Research works on acceleration have found its' positive effects on gifted students' academic performance and social/emotional development (Lubinski & Benbow, 2006;Stanley, 2000;Cornell et al, 1991;Brody et al, 1990;Neihart, 2007;Tiesco, 2003). In particular, the PERMATApintar TM College's educational program focuses on the options of grade acceleration and content acceleration.…”
Section: Permatapintar Tm College Education Programmentioning
confidence: 99%
“…They were choosing to pursue other advanced degrees. Achievement in math and science careers also relies upon spatial ability, a consideration of verbal ability, preferences as to working with people versus working with things, and the amount of time one is willing to devote to one's career (Lubinski & Benbow, 2006). Spelke (2005) addressed the issue of men and women having equal cognitive capacity for math and science careers.…”
Section: Chapter 2: Plenary Literature Review the Current Situationmentioning
confidence: 99%